Nuevos registros de royas (Uredinales) de Nigeria - JOSÉ R. HERNÁNDEZ; DAN O. EBOH; AMY Y. ROSSMAN (Caldasia)
Five species of rust fungi from Nigeria are treated. Coleosporium plumeriae and Puccinia mogiphanis (originally from tropical America ) are reported for the first time from África. Hemileia chlorocodonis is reported for the first time in Nigeria and on a new host, Tacazzea apiculata (Apocynaceae). Descriptions and comments are provided for the relatively rare species Dietelia codiaei and Endophyllum cassiae.